A functional approach for managing ITER operations - van Houtte, Didier; Sagot, François; Okayama, Katsumi; Blackler, Kenneth (Fusion engineering and design, 2012)
► A function-oriented approach for defining and organizing all the functions required to perform the mission has been developed. ► A Functional Breakdown Structure providing a complete hierarchy of functions on multiple levels is presented. ► The FBS is used for giving a good visibility of ITER project needs and requirements. ► Reliability (R) and Inherent Availability (AI) of basic functions are calculated from data on the structures, systems and components (failure rate and time to repair) for obtaining the Availability objectives of the ITER project. ITER is currently the most ambitious project on nuclear fusion research. Its objective is to demonstrate the feasibility of fusion as an energy source for the future. The complexity of the systems required to meet this challenge present many opportunities for omissions or incorrect assumptions. System engineering allows the engineer to deal with such a complexity by developing a Functional Breakdown Structure (FBS). Unlike a Plant Breakdown Structure (PBS), the FBS is a function-oriented tree, not a product-oriented tree. It details operations or activities that have to be performed as needed functions of the architecture, allowing identification of any missing elements, defining the personnel skills required to operate the architecture and managing the machine availability.